Valoración Paisajística y Socio Ambiental del páramo de la comunidad San José de Poaló del cantón Píllaro. Propuesta de Conservación, 2023 - Moposita Toapanta, Jimena Anabel (2024)
The landscape is a scarce, valuable natural resource with growing demand, easily depreciable and hardly renewable, the visual landscape considers aesthetics and perception capacity of one or more people. The research project is developed based on the landscape assessment, with the objective of identifying the quality of the conditions of the natural landscape within the community of San José de Poaló, located in the Parish of San José de Poaló in the Province of Tungurahua. For it The analysis of the conditions of the natural landscape that the community has was established and a methodology focused on the identification of landscape units was proposed. which are: the Bureau of Management “BLM” method and the capacity method visual absorption “CAV”, which helped distinguish fragility and sensitivity of the landscape in the strategic points sampled, this based on values qualitative variables established in various numerical weighting scales focused on the determination of the components (texture, color, relief, erodibility, slope, vegetation, context among others.) that are part of the units of the landscapes, based on subjective assessments presented by the researcher through analysis of photographs taken in the field and surveys carried out with a population of 40 families, which lead to knowing the different activities they carry out in the place. As a result, it was established that the moor has an average visual quality class B, where its areas have variety in shape, color, line and texture but that is common in the region studied with an average of 17, the capacity of visual absorption presents an average of 14, which belongs to class III, which means that the visual quality is not very fragile, while the fragility of the landscape of the moor yielding an average of 17 belonging to class II, which represents a moderate landscape. It is concluded that there is a need to establish plans and policies of conservation, regeneration and restoration in the strategic areas of the area of study.